Clinical value of antibodies to lysobisphosphatidic acid in patients with primary antiphospholipid sindrome - S. Giunco (Reumatismo, 2011)
To assess the clinical value of anti-lysobisphosphatidic acid (anti-LBPA) antibodies in patients with primary antiphospholipid syndrome (APS), the sera of 140 primary APS patients were tested and compared with those of 70 control subjects affected with rheumatic systemic diseases (n. 24) or autoimmune thyroiditis (n. 46). Anti-LBPA anticardiolipin (aCL) and anti-β2 Glycoprotein I (anti-β2GPI) antibodies were determined using a “home made” ELISA method. Lupus anticoagulant (LA) was assessed using a series of clotting tests in accordance with the literature. IgG anti-LBPA was significantly prevalent in primary APS (p=0.000) with a sensitivity of 58.6% and a specificity of 92.9%. IgM anti-LBPA showed a significant frequency in primary APS (p=0.000) with a sensitivity of 28.6% and a specificity of 97.1%. Anti-LBPA’s sensitivity and specificity for APS were lower or equal to those of aCL and anti-β2GPI. The prevalence of anti-LBPA in the different clinical and laboratory subsets of APS was lower than those of aCL and anti- β2GPI. It is interesting to observe that both IgG and IgM anti-LBPA were never found alone. The comparison between anti-LBPA and LA showed that the former had a higher sensitivity but a lower specificity. In conclusion, in view of our results anti-LBPA cannot at present be considered a further tool to be utilized to diagnose APS and to differentiate the different clinical and laboratory subsets of this disease.